Consumer poultry handling behaviors - Donelan, Amy K. (Kansas State University, 2015)
Understanding how consumers handle poultry can highlight gaps in consumer knowledge and practice of food safety. Quantitative research provides only a partial image, whereas qualitative data is helpful in gaining a complete picture of a shopper's behaviors. The objective of this study was to determine what poultry product microbes could potentially be transferred during purchasing and home storage; using a shop-along observational technique to observe actual shopping, transporting, and storing behavior of consumers with raw poultry products. In 71% (n=97) of the situations observed there was no visible hand sanitizer or wipes in the meat section of the grocery store. Plastic bags could be found in the meat section 85% (n=97) of the time, which only 25% of shoppers (n=82) used the bag for their poultry products. During transportation, the consumer bagged the poultry separately from other products in 71% of the observations. A majority of shoppers (59%) stored poultry without using a plastic bag or other container. Overall, there needs to be an increase in food safety education on the handling of poultry during purchasing, transporting, and storage.
Keywords: Poultry; Food safety; Consumer; Shop- along; Behavioral Sciences (0602); Food Science (0359)